2016
DOI: 10.1007/s00247-015-3531-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two single-breath-held 3-D acquisitions with multi-breath-held 2-D cine steady-state free precession MRI acquisition in children with single ventricles

Abstract: Three-dimensional k-t SSFP and 3-D multiple SENSE for ventricular volumetry release the constraints of multiple breath-holds in children and overcome problems related to interslice misalignment caused by inconsistent amplitude of breathing. Three-dimensional multiple SENSE SSFP performed better in our pediatric population than 3-D k-t SSFP. However, these 3-D sequences produce lower-quality diagnostic images than the gold standard 2-D breath-held SSFP sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Therefore, one BH CSC protocol with a lower view per segment would be a more feasible approach. A previous study (9) indicated that sensitivityencoding sequences produced lower-quality diagnostic images and moderate artifact and noise than that produced by the gold standard 2D BH balanced steady-state free precession cine (8). CS could remove the artifacts in the image and improve the image quality as much as possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, one BH CSC protocol with a lower view per segment would be a more feasible approach. A previous study (9) indicated that sensitivityencoding sequences produced lower-quality diagnostic images and moderate artifact and noise than that produced by the gold standard 2D BH balanced steady-state free precession cine (8). CS could remove the artifacts in the image and improve the image quality as much as possible.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced BHs and scan time would improve patients' compliance, and accelerated SA cine acquisition can be an acceptable approach. Accelerated CMR cine techniques [such as k-t blast, parallel imaging, and compressed sensing (CS)] have been used in the quantitative assessment of ventricular volume and function (8)(9)(10). Both scan time and BHs were reduced drastically when parallel imaging or CS techniques were used.…”
Section: Introductionmentioning
confidence: 99%
“…Free-breathing bSSFP can be partially overcome using multiple signal averaging or respiratory gating, but usually at the expense of degraded image quality or increased scan time [5,6]. Moreover, several studies have reported signi cant differences, especially in right ventricular (RV) volumetry results obtained from the respiratory-triggered bSSFP image [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Retrospectively cardiac‐gated cine balanced steady state free precession (bSSFP) images acquired during breath‐hold in short‐axis (SAx) orientation can establish high accuracy and reproducibility for functional assessment 7–10 . However, cine bSSFP imaging remains challenging for patients with limited breath‐holding capacity, as it requires multiple consecutive short breath‐holds (eg, 12 to 16 breath‐holds of 5–6 seconds each) or fewer relatively longer breath‐holds (eg, 6–8 breath‐holds of 10 to 12 seconds) 11,12 . In the case of pediatric patients with heart disease and other comorbidities, the challenges associated with breath‐holds are more pronounced due to diminished breath‐holding capacity, limited ability to cooperate, and anxiety of the closed bore environment of the MRI scanner 13 .…”
mentioning
confidence: 99%
“…breath-holding capacity, as it requires multiple consecutive short breath-holds (eg, 12 to 16 breath-holds of 5-6 seconds each) or fewer relatively longer breath-holds (eg, 6-8 breathholds of 10 to 12 seconds). 11,12 In the case of pediatric patients with heart disease and other comorbidities, the challenges associated with breath-holds are more pronounced due to diminished breath-holding capacity, limited ability to cooperate, and anxiety of the closed bore environment of the MRI scanner. 13 The requirement for shorter breath-hold duration to minimize respiratory motion competes with the longer breath-hold needed to accommodate the increased spatial and temporal resolution essential for capturing the intricate details of smaller cardiac structures and the rapid changes in heart dynamics characteristic of this young population.…”
mentioning
confidence: 99%